O surgimento dos Cultos a Carga : encontros e conflitos no contexto intercultural e colonial da Melanésia e Papua Nova Guiné - Flora, Luciney Paulino (2012)
The present dissertation accomplished a study about the emerging of the Cargo Cults in the dynamic of encounters and conflicts in Melanesia and Papua New Guinea s intercultural and colonial context. Its main aim was: 1) to analyse the colonization process and its impact on Melanesia and Papua New Guinea s society, culture and religions, emphasising the missionary actions, e 2) to make an approximation and reading of the Cargo Cults development through the historic relations that follows the encounter between occidental culture and traditional cultures . As methodological resource it conjugated the concepts of cultural negotiation , cultural translation , transculturality , cultural appropriation and syncretism , making a reading witch try to surpass the old binary s approaches of reflections that looked at the Western and Traditional societies as closed totalities. From the interpretation process of the research s composition, it was concluded that the colonial circumstance and the missionaries presence brought about a new reality, of conflict and constant cultural negotiation. Cargo Cults were seen as expression of that new reality. The research showed that in this cultural negotiation process there are losses, but also earnings to both sides